Preensão das estrelas : astronomia amadora, ciência conectada e teoria ator-rede - Couto, Walter Eler do (2016)
Amateur astronomers and Networked Science call into question a series of binary distinctions traditionally found in books of epistemology and science studies (e.g., centre of calculation or periphery of calculation? exoteric or esoteric circles? literature or digital networks of propagability? Is there science without the construction of new knowlege? How to make a boundary?). Networked Science is remodelling, for instance, the work of scientific researchers, subverting the "science of academic journals". Such a subversion compels us to make a thorough reconsideration of the nature of scientific communication. Changes such as the ones related to the forms of transmitting scientific material using the Internet (from raw data to finished articles), the formation of discussion groups, and serendipity generators, that operate the "collective intelligence", are present in the most diverse fields. Today, many science divulgation problems are solved due to a complex system of propagability of information through social networks. There are many different forms of studying this event; one of them occurs under the viewpoint of the non-scientist, or the non-professional, who ends up gaining acess to the contents of Networked Science. He not only accesses the contents, but uses the same Internet mechanisms to execute his amateur activities, contributing both to the production of new contents and to the propagation of the preexisting ones. It is at this point that the theme of "Networked Science" meets the fundamental problem of this work: the amateurs. With this end in view, we perform multi-sited virtual ethnographies of Pro-Am (professional-amateur) collaborative projects, Citizen Science projects and social networks of serendipity and propagability (amateur-amateur collaboration), describing and problematizing a series of compositions in amateur astronomy that occur in a virtual environment. Through theoretical debates involving the so-called contemporaneous epistemes (Latour, Stengers, Fleck, Mol, Nielsen, Whitehead, Sloterdijk), we draw a series of considerations regarding the political-epistemological relationships of between professionals and amateurs. From that, we endeavor to discuss also the relations that the modern sciences (as institutions) maintain with their diverse ancestral avatars, such as natural history and natural philosophy. All this may result in deep debates about classical themes of political epistemology, like the very definition of knowledge, the boundaries between science and non-science and disciplined progress.